2018
DOI: 10.1007/s11657-018-0475-z
|View full text |Cite
|
Sign up to set email alerts
|

Severe hypoglycemia is associated with high risk for falls in adults with type 1 diabetes

Abstract: This is the first study on prevalence and risk factors for falls suggesting that falls are common in T1D and severe hypoglycemia is a unique diabetes-related factor associated with threefold higher risk for falls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 17 publications
2
21
0
2
Order By: Relevance
“…comprehensive geriatric assessment) (https://www.nice.org.uk/guidance/cg161). According to the STEADI initiative and the NICE guidelines, the management of patients at risk of falling starts with the management of conditions that alter gait, balance and mobility such as postural dizziness and postural hypotension, cognitive impairment, metabolic abnormalities such as hypoglycaemia [48] or hyponatraemia [49], sleep disturbances [50], muscle weakness and urinary incontinence [47] and conditions that induce fainting. Insertion of a pacemaker should be considered for older people with frequent falls associated with cardioinhibitory carotid sinus hypersensitivity, or sinus node dysfunction, conditions which cause sudden changes in heart rate and blood pressure [32,51].…”
Section: Multifactorial Falls Risk Assessment and Interventions In Patients With High Risk Of Fallingmentioning
confidence: 99%
“…comprehensive geriatric assessment) (https://www.nice.org.uk/guidance/cg161). According to the STEADI initiative and the NICE guidelines, the management of patients at risk of falling starts with the management of conditions that alter gait, balance and mobility such as postural dizziness and postural hypotension, cognitive impairment, metabolic abnormalities such as hypoglycaemia [48] or hyponatraemia [49], sleep disturbances [50], muscle weakness and urinary incontinence [47] and conditions that induce fainting. Insertion of a pacemaker should be considered for older people with frequent falls associated with cardioinhibitory carotid sinus hypersensitivity, or sinus node dysfunction, conditions which cause sudden changes in heart rate and blood pressure [32,51].…”
Section: Multifactorial Falls Risk Assessment and Interventions In Patients With High Risk Of Fallingmentioning
confidence: 99%
“… 3 Exercise can improve glycemic control 17 and sensitivity to exogenous insulin, 18 and was shown to reduce the risk of falls and fractures in the elderly in a Cochrane review, 47 a complication that individuals with type 1 diabetes are highly vulnerable to. 48 Yet exercise rates are lower in those with type 1 diabetes, with reasons including fear of hypoglycemia, uncertainty about how to control blood sugars around exercise, and diabetes complications. 17 Our data show that those with type 1 diabetes still benefit from the acute effects of exercise on bone turnover.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported increased risk of fractures due to hypoglycemic events,69,70 whereas other studies found no association 9,52,53. Although evidence on hypoglycemia and fracture is conflicting, hypoglycemia is associated with falls61 and hypoglycemia may be widely underdiagnosed in studies that mainly use registries and questionnaires. Thus, the true prevalence of fractures due to hypoglycemia is susceptible to be larger than what is presented in the literature.…”
Section: Impact Of Medications On Fracture Riskmentioning
confidence: 99%
“…One study reported increased fracture risk in patients with T1D and no complications 60. Although the association between diabetes complications and fracture risk remains controversial, a study reported that 41% of patients with T1D are fearful of falls, and that the main contributors to falls are neuropathy and hypoglycemia 61. A severe limitation to the studies assessing diabetes complications, falls, and fracture risk is that the data is mainly collected through registries and questionnaires, and therefore patients may be misclassified by both diabetes diagnosis (e.g.…”
Section: Influence Of Complications and Comorbidities On Fracture Riskmentioning
confidence: 99%